Evaluation of the Emerging Multidrug- Resistant Acinetobacter baumannii in Clinical Samples from Tertiary Care Hospitals in Mysore, India - a Cohort Study (Asian Journal of Pharmaceutics (AJP), 2021)
Objectives: Acinetobacter baumannii is an important emerging nosocomial pathogen of alarming significance.It has the propensity not only to cause much morbidity and mortality, but is also leading to the uselessness of theavailable limited antibiotic drugs due to the rampant resistance. Materials and Methods: The present study aimsto document and evaluate the current situation on the available treatment options for A. baumannii nosocomialinfection, mainly the carbapenem drug- imipenem, colistin, and tigecycline and to analyze the drug safetyand any/all of the adverse drug reactions related to this drug therapy. Results: Results of this study probe thatcarbapenem resistance is seen in about 86% of all Acinetobacter isolates. Colistin is the best available treatmentfor multi-drug resistant species with 100% cure rate and fewer serious life threatening adverse effects with the longduration therapy that is required in this case. The only concern remained the patient compliance to the abdominalsymptoms (56.7% of nausea, 14.43% vomiting and 4.12% diarrhea) which was statistically significant (P = 0.049).Conclusion: Overall, colistin therapy can be regarded as the best treatment for multi-drug resistant A. baumannii,which opens avenues for further studies on the pharmacokinetics and pharmacodynamics of this drug.